Even Though the Long Distance: Are We Still Going on? Dyadic Trust, Relationship Maintenance Behaviors, and Relationship Quality Among Emerging Adulthoods - Korun, Ali Berke; Satici, Seydi Ahmet (WILEY, 2026)
Long-distance romantic relationships have become an increasingly common type of relationship. Especially among emerging adults, the preference for such relationships is increasing. This situation reveals the importance of analyzing how long-distance relationships are maintained and the quality that individuals perceive from these relationships. The study group of this research consists of emerging adults who have been in a long-distance romantic relationship for at least 6 months. The study examined the relationships between relationship maintenance behaviors, dyadic trust and relationship quality. The findings obtained using a serial mediation model show that relationship maintenance behaviors predict relationship quality both directly and indirectly through dyadic trust. In particular, openness and positivity play important roles in the formation of trust, which in turn increases overall relationship quality. The results emphasize that adaptive communication and relationship maintenance behaviors play a critical role in overcoming the difficulties encountered in long-distance relationships. The findings are discussed within the framework of family systems theory and the impact of stressors on the system and the role of effective relationship maintenance behaviors in maintaining relational balance and functioning are discussed. Finally, implications for practice and future research in the field of relationship counseling are discussed.
Keywords: dyadic trust; emerging adulthood; long-distance relationships; relationship maintenance behaviors; relationship quality; ROMANTIC RELATIONSHIPS; PARTNER SUPPORT; SATISFACTION; STRATEGIES; ATTACHMENT; STABILITY; Psychology